(3GdJcGdja dCZQGV GdJNWjW h GdQbGHI (B:s (3OQGSGJ fXQjI h JWHjbjI eJYebI (B/s - (3eQYj, YHO GdMjs; (3WGMhf, eMeO YHO GdMejOs ((3GdGScfOQjI(B: s (3OGQ GdeWHhYGJ GdLGeYjI(B, s, 2008)
(3GdHGH GdGhd (B: (3bjGS GdJcdaI dGZQV GdJNWjW eY GdJQcjR Ydi GdaJQI GdbUjQI j JNWjW hJfXje hQbGHI GdYedjGJ GdLGQjI JNWjW GdGgOGa , aj GdYdGbI Hjf GdJcdaI hGdMLe hGdQHM , aj eONd GdJcGdja GdeHGTQI hGSJNOGeGJg , aj GdJcdaI dGZQGV JNWjW GdGSJeQGQ aj GdYedjI GdGfJGLjI aj GdeOi GdWhjd GdHGH GdKGfj aj bjGS GdJcdaI dGZQGV GdQbGHI ebOeI aj fXGe GdQbGHI Ydi GdJcGdja fXGe GdeMGSHI GdeSDhdjI , OhQ GdeYGjjQ hGdehGRfGJ aj GdQbGHI Ydi GdJcGdja , JMdjd GfMQGaGJ GdCQHGM heSHHGJgG , JMdjd hJaSjQ GfMQGaGJ GdehGO GdeHGTQI hGdYed GdeHGTQ JMdjd GfMQGaGJ GdJcGdja GdGVGajI GdUfGYjI , aj GdJcGdja GdeYjGQjI dGZQGV JMOjO JcdaI GdGfJGL ,aj GdJcGdja GdeYjGQjI hGdGSGdjH GdGMUGFjIs
Keywords: (3GdJNWjWs; (3GdQbGHI GdeGdjIs; (3eMGSHI GdJcGdjas